A Point Mutation in Nucleoside Diphosphate Kinase Results in a Deficient Light Response for Perithecial Polarity in Neurospora crassa - Ogura, Yasunobu; Yoshida, Yusuke; Yabe, Naoto; Hasunuma, Kohji (The Journal of biological chemistry, 2001)
In Neurospora crassa, the phosphorylation of nucleoside diphosphate kinase (NDK)-1 is rapidly enhanced after blue light irradiation. We have investigated the function of NDK-1 in the blue light signal transduction pathway. A mutant called psp (phosphorylation ofsmall protein) shows undetectable phosphorylation of NDK-1 and is defective in light-responsive regulation of perithecial polarity. Sequencing analysis ofndk-1 cDNA by reverse transcription-polymerase chain reaction revealed that proline 72 of ndk-1 was replaced with histidine in psp. The mutation ndk-1P72H resulted in accumulation of normal levels of mRNA and of about 25‥ of NDK-1P72Hprotein compared with that of wild type as determined by Western blot analysis. The ectopic expression of cDNA and introduction of genomic DNA of wild type ndk-1 in psp(ndk-1P72H) suppressed the reduction in accumulation and phosphorylation of NDK-1 and the light-insensitive phenotype. These findings demonstrated that the phenotype ofpsp was caused by the ndk-1P72Hmutation. Biochemical analysis using recombinant NDK-1 and NDK-1P72H indicated that the P72H substitution in NDK-1 was responsible for the decrease in phosphotransfer activities, 5‥ of autophosphorylation activity, and 2‥ of Vmaxfor protein kinase activity phosphorylating myelin basic protein, compared with those of wild type NDK-1, respectively.